Vestibular stimulation by 2G hypergravity modifies resynchronization in temperature rhythm in rats - Tristan Martin (Nature Portfolio, 2020)
Abstract Input from the light/dark (LD) cycle constitutes the primary synchronizing stimulus for the suprachiasmatic nucleus (SCN) circadian clock. However, the SCN can also be synchronized by non-photic inputs. Here, we hypothesized that the vestibular system, which detects head motion and orientation relative to gravity, may provide sensory inputs to synchronize circadian rhythmicity. We investigated the resynchronization of core temperature (Tc) circadian rhythm to a six-hour phase advance of the LD cycle (LD + 6) using hypergravity (2 G) as a vestibular stimulation in control and bilateral vestibular loss (BVL) rats. Three conditions were tested: an LD + 6 exposure alone, a series of seven 2 G pulses without LD + 6, and a series of seven one-hour 2 G pulses (once a day) following LD + 6. First, following LD + 6, sham rats exposed to 2 G pulses resynchronized earlier than BVL rats (p = 0.01), and earlier than sham rats exposed to LD + 6 alone (p = 0.002). Each 2 G pulse caused an acute drop of Tc in sham rats (−2.8 ± 0.3 °C; p < 0.001), while BVL rats remained unaffected. This confirms that the vestibular system influences chronobiological regulation and supports the hypothesis that vestibular input, like physical activity, should be considered as a potent time cue for biological rhythm synchronization, acting in synergy with the visual system.